2015
DOI: 10.1007/s00276-015-1581-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the pelvic lymph node normal size? Determination from normal MRI examinations

Abstract: The mesorectum nodes should be considered as abnormal when they are over 4 mm in short diameter. For the other node areas, the upper limits of the normal range were, respectively, 6, 6, 5, 7 mm for the external and common iliac, internal, iliac and inguinal nodes for the short axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
4
5
0
1
Order By: Relevance
“…To our knowledge, this is the first report regarding preoperative LN evaluation with ultrasound for EMPD in the genital area. The longitudinal and transverse diameters of non‐metastatic LN in our study were larger than those of normal inguinal LN in the previous report, suggesting that regional LN are usually enlarged by inflammation in the primary lesion. However, longitudinal and transverse diameter alone is insufficient to distinguish between metastatic and non‐metastatic LN.…”
supporting
confidence: 73%
“…To our knowledge, this is the first report regarding preoperative LN evaluation with ultrasound for EMPD in the genital area. The longitudinal and transverse diameters of non‐metastatic LN in our study were larger than those of normal inguinal LN in the previous report, suggesting that regional LN are usually enlarged by inflammation in the primary lesion. However, longitudinal and transverse diameter alone is insufficient to distinguish between metastatic and non‐metastatic LN.…”
supporting
confidence: 73%
“…Attempts have been made to define different upper size limits of normal lymph nodes for the different abdominal and pelvic territories [9]. The most recent study in this series demonstrated a 1.5 T MRI-determined threshold for suspicious mesorectal nodes of 4 mm and 6 or 7 mm for all other pelvic territories [10]. The mean sizes of normal lymph nodes in this study varied between 2.6 and 3.9 mm.…”
Section: Current Imagingmentioning
confidence: 53%
“…However, these criteria are used in the clinical practice and do not depend on any imaging method. In a limited number of studies assessing size of normal inguinal lymph nodes on different imaging modalities in adults, upper limit of short axis diameter of inguinal lymph nodes varies between 7-15 mm [1,4,9,10]. The study evaluated inguinal lymph nodes in asymptomatic patients on CT revealed a mean short axis of 5,4 mm, and a value of 8,8 mm at 2 SD above the mean for all inguinal lymph nodes [1].…”
Section: Discussionmentioning
confidence: 98%
“…There have been very few studies providing information about size range and imaging characteristics of normal inguinal lymph nodes in adult age group [1,4,9,10]. However, to our knowledge, there have been neither established size criteria nor a study assessing imaging characteristics and distribution of inguinal lymph nodes on CT in children.…”
Section: Introductionmentioning
confidence: 99%